PERBEDAAN KECERDASAN EMOSIONAL, PERILAKU BELAJAR dan TINGKAT STRES MAHASISWA AKUNTANSI JUNIOR DAN SENIOR - Fidiana Fidiana; Lydia Setyawardani (EKUITAS (Jurnal Ekonomi dan Keuangan), 2009)
The objective of this paper is to test empirically emotional intelligence and learning behaviour that influence stress as dependent variable and to prove the differences of stress level, emotional quotien, and  learning behavior among junior and senior students.  Population of this study are students at Accounting Department of Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya. Based on purposive sampling and convenience sampling method there are 306 accounting students as sample of the research.  Hypotheses were tested using multiple regression analysis model and Mann-Whitney U test. Based on model used, the results with F-test or Anova provide evidence that both emotional intelligence and learning behavior have significant influence on stress. Based on the Mann-Whitney U test, there are significant differences of stress level, emotional quotien, and learning behavior among junior and senior students. The limitation of this paper is the population just consists of STIESIA students, so the results can not be generalized